Penilaian Status Sumber Daya Air untuk Mitigasi Bencana Banjir dan Kekeringan: Studi Kasus Sub DAS Madiun: Assessment of Water Resource Status to Mitigate Flood and Drought Disasters: Case Study Madiun Sub Basin - Alfia Surya Rahmanda; Bambang Dwi Dasanto (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2018)
Bengawan Solo river flow through into Madiun Sub Basin causes overflow river and drought. Moreover, relatively unstable water demand causes imbalance of water balance. Potency of flood and drought can be identified based on a water resources status in the studied area. To achieve target it, this research focused on three main stages; firstly, calculating water demand and water availability; secondly, analyzing water balance; and, thirdly, assessing water resources status. Water balance (supply-demand) method has been used to finish three aims or target from this research. Water supply was calculated based on volume of water availability, while total volume of water demand was counted from three water demand sectors, i.e. domestic, industrial, and agricultural. The results showed that the highest the water demand sourced from agricultural sector; meanwhile, the lowest the water demand was from domestic sector. Based on water balance analysis, Madiun Sub Basin has experienced a water deficit in 2012, 2014 and 2015. The most severe water deficit occured in 2012, because river discharge in the research area experienced decreasing during this year. The assessment of water resource status each month in Madiun Sub Basin is predominantly 3; this condition indicated that the region experienced high water stress.